Aleurf Wa'atharah Fi bath Almasayil Alfaqhiat Namadhij Tatbiqiat Eamalia - Jasim, Wissam (Islamic Sciences Journal, 2023)
ABSTRACT In the research which is entitle ,Custom and its effect on some doctrinal issues) I talked about custom as one of the guides of the Sharia according to the agreement of the four schools of thought and took some practical models that affect people's daily life, but are repeated daily for more than once for tens or hundreds of times or more by the total of people and their dealings For example (food) , drink in the sale, and the sale of misuse) is not free for an hour or a minute but people deal with it, and divided it into two topics. The first topic in which I spoke about custom language and convention, and building judgments on it, its health, evidence and conditions of work in it . The second topic dealt with some of the applied issues which are the expense of treating the wife, food and drink in selling, sale of abuse, certificate of immorality with injustice or its weakness, marriage of authorization and dowry of the parable, then the conclusion, sources and references.